2020
DOI: 10.1590/1806-93042020000200003
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spontaneous abortion: a systematic review

Abstract: Objectives: to compile studies produced regardinggenetic and non-genetic risks factors associated with occurrence of spontaneous abortion. Methods: it talks about a systematic review article, with studies between January of 2008 to November of 2018 according to SciELO, PubMed, Lilacs and BVS. Results: in total, 567 articles were found. After applying the definedeligibility criteria, 44 articles made part of the review, being the majority published on Asia between 2008 and 2011, and 10 articles published on B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
7
0
10
Order By: Relevance
“…One important aspect of pregnancy loss involves its risk factors. Among the many risk factors for miscarriage, researchers have highlighted the mother’s age, socio-economic standing, nutritional status, and substance use; history of obstetric problems such as miscarriage, premature labor, cesarean section, or gestational diabetes mellitus; performing physical labor requiring heavy lifting; stress; infections; and hormonal factors [ 24 , 25 , 26 , 27 ]. Both maternal age above 35 years and multiple previous deliveries increase the risk of miscarriage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One important aspect of pregnancy loss involves its risk factors. Among the many risk factors for miscarriage, researchers have highlighted the mother’s age, socio-economic standing, nutritional status, and substance use; history of obstetric problems such as miscarriage, premature labor, cesarean section, or gestational diabetes mellitus; performing physical labor requiring heavy lifting; stress; infections; and hormonal factors [ 24 , 25 , 26 , 27 ]. Both maternal age above 35 years and multiple previous deliveries increase the risk of miscarriage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A body of studies have revealed that lower SES is one of the most common risk factors associated with adverse pregnancy or neonatal outcomes, including stillbirth, neonatal mortality, congenital heart disease and spontaneous abortion [22]. Besides, consistent evidence across many countries has indicated that people in lower SES suffer more from inadequate intake and deficiency of vitamin D [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os principais fatores genéticos, destacam-se as anormalidades cromossômicas e polimorfismos; dentre as causas não genéticas, estão os processos infecciosos, causas socioeconômicas, ambientais, distúrbios endócrinos e trombofílicos. Por outro lado, cerca de 50% dos casos de abortamento apresenta-se como causas desconhecidas (Oliveira et al, 2020).…”
Section: Introductionunclassified
“…Por ocorrer de forma tão precocemente, muitas vezes, inicialmente a etiologia é considerada desconhecida. Nesse sentido, sua incidência é estimada em 15 a 20% de todas as gestações, sendo a maioria destes nas primeiras semanas de gestação (Oliveira et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation